The complete three-vessel view in prenatal detection of congenital heart defects - Tongsong T. (2014)
Objective: To evaluate the effectiveness of the complete three-vessel view (c3VV) in assessment of fetuses with prenatally diagnosed congenital heart defects (CHD). Methods: Fetuses with prenatal suspicion of CHD were prospectively recruited into the study. All examinations included a c3VV for assessment of abnormalities in alignment, arrangement, vessel size, number of vessels, aortic arch sidedness and color flow mapping. Definite diagnoses of CHD were based on neonatal cardiologic exams or postnatal autopsy. Results: Of 106 consecutive fetuses with CHD, 75 were shown to have at least one abnormality on the c3VV, a detection rate of 70.8%. When septal wall defects were excluded, the detection rate increased to 89%. All cases of transposition of great arteries (TGA), aortic stenosis, pulmonary stenosis, truncus arteriosus and ductal aneurysm showed abnormal c3VV. Additionally, abnormal c3VV was also visualized in most cases of double outlet right ventricle (DORV), Ebstein's anomaly and tricuspid atresia. Among the 75 fetuses with congenital heart defects detected at c3VV, some defects had several abnormalities visualized at c3VV. Of interest, two vessels on the c3VV were seen in all five cases of TGA, in all three cases of truncus arteriosus and in one-third of DORV cases. Conclusion: This prospective descriptive study demonstrates that the c3VV has high detection rate in identifying clues for the presence of CHD, especially when excluding septal wall defects. Thus, c3VV could probably be used as part of routine screening for CHD. Copyright © 2009 John Wiley & Sons, Ltd.